2023
DOI: 10.3389/fpls.2023.1177345
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTL, QTL-by-environment interactions, and their candidate genes for resistance HG Type 0 and HG Type 1.2.3.5.7 in soybean using 3VmrMLM

Abstract: IntroductionSoybean cyst nematode (SCN, Heterodera glycines Ichinohe) is an important disease affecting soybean yield in the world. Potential SCN-related QTLs and QTL-by-environment interactions (QEIs) have been used in SCN-resistant breeding.MethodsIn this study, a compressed variance component mixed model, 3VmrMLM, in genome-wide association studies was used to detect QTLs and QEIs for resistance to SCN HG Type 0 and HG Type 1.2.3.5.7 in 156 different soybean cultivars materials.Results and discussionThe res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, there were no overlapping sites between QEI and QTNs detected based on two environmental data, indicating that all QEIs had no significant additive or dominant effect, but only the interaction effect between additive or dominant and environment, while all the QTNs in twoenvironment jointly analyze were opposite. Using the same 3VmrMLM method in previous studies, the overlapping sites between QEI and QTNs were also few, ranging from 1-3 sites (Han et al, 2022;He et al, 2022;Yu et al, 2022;Zhang et al, 2022;Jiang et al, 2023;Zhao et al, 2023), except for the study of Zou et al (2022), which found 13 overlapping sites. From the perspective of the effect of QEI, since most QEIs do not have a significant additive or dominant effect, their reliability needs to be further confirmed.…”
Section: Discussionmentioning
confidence: 87%
“…However, there were no overlapping sites between QEI and QTNs detected based on two environmental data, indicating that all QEIs had no significant additive or dominant effect, but only the interaction effect between additive or dominant and environment, while all the QTNs in twoenvironment jointly analyze were opposite. Using the same 3VmrMLM method in previous studies, the overlapping sites between QEI and QTNs were also few, ranging from 1-3 sites (Han et al, 2022;He et al, 2022;Yu et al, 2022;Zhang et al, 2022;Jiang et al, 2023;Zhao et al, 2023), except for the study of Zou et al (2022), which found 13 overlapping sites. From the perspective of the effect of QEI, since most QEIs do not have a significant additive or dominant effect, their reliability needs to be further confirmed.…”
Section: Discussionmentioning
confidence: 87%
“…Some of these genes, for example found at the rhg2 locus, remain to be cloned (Suzuki et al 2020). Other sources of genetic resistance to H. glycines have since been identified as it is an ongoing process (Wen et al 2017; Hua et al 2018; Jiang et al 2023; Almeida-Silva and Venancio, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It employs the association analysis to obtain all single-nucleotide polymorphisms (SNP) in the whole genome of a species and perform the correlation analysis with target traits. It estimates the effects of QTN through different models and then statistically tests the estimated effects, so as to discover the genetic variations underlying complex traits (Harold et al, 2009;Jiang et al, 2023). In addition, the rst whole-genome sequence of the variety Williams 82, completed in 2010, provides a powerful resource for soybean functional genomic research (Schmutz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%